EVALUATION OF SPERM PLASMA MEMBRANE INTEGRITY OF FROZEN-THAWED MALABARI BUCK SEMEN - VIGNESHWARAN, B; MURUGAVEL, K; ANTOINE, D (The Indian Journal of Animal Reproduction, 2023)
The present study was aimed to establish the best hypo-osmotic solution for evaluating membrane integrity in frozen-thawed Malabari buck semen. Sodium citrate and fructose based solutions with different osmolarities (50, 75, 100, 125, 150, 175 and 200 mOsm/L) were compared in 54 frozen-thawed semen samples. Based on the observations, 50 mOsm/L was found to be the most suitable hypo-osmotic solution for HOST.